Arduino welding table / Adli Adham Abdul Hakim - Abdul Hakim, Adli Adham (2022)
This Final Year Project (FYP) is called Arduino Welding Table. It is a welding table that can be controlled by Internet of Things (IoT) system. This project consists of a skill in coding and work in welding. Firstly, to do this project it is required a coding from Arduino IDE applications to make Arduino works properly when the instructor run the test on the table. The aims of this study are to create a safety awareness welding environment for the welder instructor and to educate students to know the welding process using the Internet of Things (IoT) system. After that, the original welding table that placed in welding workshop is measured accurately and precisely then illustrate in the solidwork software. A danger always happens while doing the welding process. It can lead to major injuries to the welder such as spark & damage to the person. Then, welding work is usually done in a classical way that more likely does not have any types of safety features for the welder when doing the welding process. The solidworks software will create a model of this Arduino Welding Table that works just like the real project when it finishes. Then, the Arduino Uno then install to the demonstrate welding table followed the illustration that have made in solidwork software. Lastly, the Arduino Welding Table is tested by creating a real process of Gas Metal Arc Welding (GMAW). With this method, it can sense any of error of this Arduino Welding Table either it is from Arduino coding or a mistake at its installations. Some of the functions of this Arduino Welding Table is, it can detect any fire that can be caused by spark of the welding. This Arduino Welding Table is expected can run with the safety features and can works perfectly with IoT system as illustrated in solidworks. To conclude this Final Year Project (FYP), this project can reduce the risk of danger to the instructor.